Updating the check list: new records of Psocodea (Insecta) from French Guiana - Dilian Georgiev (Historia naturalis bulgarica, 2025)
This paper reports six psocid species as new records to French Guiana: Echmepteryx madagascariensis (Kolbe, 1885), Lepidopsocus marmoratus (Banks, 1931), Liposcelis bostrychophila Badonnel, 1931, Peritroctes trifasciatus Badonnel, 1981, Mesepipsocus brasilianus (New, 1972), Archipsocus cf. minutillus New, 1973. Two of them are also newly recorded for South America. A current checklist of psocid species in the department is provided, including the authors and localities where the species have been reported.